232k views
4 votes
Arrange the steps in the correct order to perform this subtraction problem 1.1 ( 10 3 ) − 4.9 ( 10 2 ) = 610

User Ncbl
by
5.7k points

1 Answer

6 votes

We are given : Expression 1.1 ( 10^3 ) − 4.9 ( 10^2 ) = 610.

Solution: In order to solve above given expression, we need to apply order of operations.

We can apply order of operations according to PEMDAS rule.

PEMDAS stands for Parentheses, Exponents, Multiplication/Division, Addition/Subtraction.

In the given problem, we need to simplify Parentheses first.

We have 10^3 and 10^2 in Parentheses.

10^3 = 10*10*10 = 1000.

10^2 = 10*10 = 100.

Substituting those values in original expression.

1.1 ( 1000 ) − 4.9 ( 100 ).

Now, we need to apply multiplication operation in 1.1*1000 and 4.9*100.

We get 1.1*1000 = 1100 and 4.9*100 = 490.

Substituting those values in above result we got.

1100-490.

Now, we can perform subtraction operation.

On subtracting 1100-490, we get 610.

And that is equal to 610.



User Frogblast
by
4.9k points